Comparison of Wenner and dipole-dipole arrays in the study of an underground three-dimensional cavity - Neyamadpour, A.; Abdullah, W.A.T.W.; Taib, S.; Neyamadpour, B. (IOP Pub Ltd, 2010)
The objective of this paper was to compare Wenner and dipole-dipole configurations in delineating an underground cavity at a site near the University of Malaya, Malaysia. A three-dimensional electrical resistivity imaging survey was carried out along seven parallel lines using Wenner and dipole-dipole arrays. A three-dimensional least-squares algorithm, based on the robust inversion method, was used in the inversion of the apparent resistivity data. In the inverted model, both the horizontal and vertical extents of the anomalous zones were displayed. Results indicate the superiority of the Wenner array over the dipole-dipole array for determining the vertical distribution of the subsurface resistivity, although the dipole-dipole array produced a better lateral extent of the subsurface features. The results show that the three-dimensional electrical resistivity imaging survey using both the Wenner and dipole-dipole arrays, in combination with an appropriate three-dimensional inversion method and synthetic model analysis, can be highly useful for engineering and environmental applications, especially for underground three-dimensional cavity detection.